2021
DOI: 10.15212/zoonoses-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Pattern Recognition Receptors in Innate Immunity to Obligate Intracellular Bacteria

Abstract: Host pattern recognition receptors (PRRs) are crucial for sensing pathogenic microorganisms, initiating innate responses, and modulating pathogen-specific adaptive immunity during infection. Rickettsia spp., Orientia tsutsugamushi, Anaplasma spp., Ehrlichia spp., and Coxiella burnetii are obligate intracellular bacteria that can replicate only within host cells and must evade immune detection to successfully propagate. These five bacterial species are zoonotic pathogens of clinical or agricultural importance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 142 publications
(252 reference statements)
0
7
0
Order By: Relevance
“…There is compelling evidence that the etiology of IBDs may be associated with various metabolic dysregulations ( Alexander et al., 2022 ; Zheng et al., 2022 ). It has been demonstrated that parasite-derived products have a strong ability to regulate metabolism in the host body ( Zhu et al., 2014 ; Cai et al., 2021 ; Fisher et al., 2021 ). Differentiation of T cells can be manipulated through modulating metabolic activity in vitro ( Chang et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence that the etiology of IBDs may be associated with various metabolic dysregulations ( Alexander et al., 2022 ; Zheng et al., 2022 ). It has been demonstrated that parasite-derived products have a strong ability to regulate metabolism in the host body ( Zhu et al., 2014 ; Cai et al., 2021 ; Fisher et al., 2021 ). Differentiation of T cells can be manipulated through modulating metabolic activity in vitro ( Chang et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammasomes are key components of the innate immune system and contribute to the initial host defense mechanism against pathogens. Inflammasomes recognize pathogen-derived molecules known as pathogen-associated molecular patterns (PAMPs) [69][70][71] as well as endogenous host-derived molecules, known as damage-associated molecular patterns (DAMPs), that are released from dying cells during stress or infection [72][73][74][75]. Inflammasomes are cytosolic multi-protein complexes that consist of intracellular nucleotide-oligomerization domain (NOD)-like receptor (NLR), nucleotide-binding domain, and leucine-rich repeat (LRR) containing proteins, or the absent in melanoma 2 (AIM2)-like receptors (ALRs), the adaptor protein apoptosis-associated speck-like protein containing a caspase activation and recruitment domain (ASC), and procaspases [76][77][78][79].…”
Section: Inflammasomes: Cytosolic Receptors With Key Roles In Intrace...mentioning
confidence: 99%
“…O. tsutsugamushi is a Gram-negative, lipopolysaccharide-negative coccobacillus, primarily infecting endothelial cells, monocytes, macrophages (MΦ), neutrophils, and dendritic cells [ 5 ]. Compared with other obligate intracellular bacteria such as Rickettsia , Ehrlichia , or Anaplasma , O. tsutsugamushi has unique yet poorly understood biology [ 6 ]. After the bacterium is internalized via endocytosis or phagocytosis, it rapidly (<4 h) escapes the endosome to freely inhabit the cytosol [ 5 ].…”
Section: Introductionmentioning
confidence: 99%